(untitled) (Archives of Mechanics - Test, 2000)
Transformation Induced Plasticity (TRIP) is demonstrated by an experimental programme for a Fe-9Ni-12Cr steel for various loading paths with partial or full unloading. The martensitic transformation is considered. A thermodynamical interpretation as well as micromechanical modelling of TRIP are presented. The selection of distinct variants is explained. Finally a modified constitutive equation for the TRIP strain rate is suggested by introducing a transformation surface including a transformation backstress. The backflow after unloading, which cannot be explained by the currently used TRIP strain rate term, can be represented by the proposed formulation. Aspects of future research are discussed.